Chemometric and computational structure–activity relationship analysis of Ziziphus jujuba and Nephrolepis cordifolia phenolics for antioxidant and antidiabetic potential - Anitha A․; Ponmurugan P․; Arunkumar D․; Vasantha Sakthi S․; Yamuna A․; Jeyapreethi S․ (South African Journal of Botany, 2026)

Fipronil, fenpropathrin and lambda cyhalothrin application alters defense related biomolecules composition favoring the resurgence of chilli thrips (Scirtothrips dorsalis) - T. Hemadri; M. Bheemanna; D. Srinivasa Reddy; Arunkumar Hosamani; R. Harischandra Naik; Saroja N. Rao; Nagaraj M. Naik; L. Rajesh Chowdary; Srikanth Barkeer; Keerthi Mc; B.L. Manisha; Wael Elmenofy; et al. (Journal of Asia-Pacific Entomology, 2026)

Study on the Mechanical, Microstructural, and Environmental Assessment of Concrete Containing High Volume Fly Ash and Waste Tyre Steel Fibers - Sankar B; Rameshkumar D; Gautham Kishore Reddy; Arunkumar K; Vishnuprasad V Prabhakar; Anamika S M (Circular Economy and Sustainability, 2026)

Exploring the physiological mechanisms and ecofriendly mitigation strategies to combat the synergistic effects of drought and high temperature stress in Setaria italica - S. Gowsiga; D. Vijayalakshmi; J. Deepika; P. Arunkumar; R. Sivakumar; U. Sivakumar; V. Yamuna (Cereal Research Communications, 2025)

Testicular thermoregulation and blood perfusion score as markers of sperm quality in summer-stressed breeding bulls - D. Lakhanpal; T. K. Mohanty; M. Bhakat; R. Arunkumar; D. Nain; R. Baithalu (Tropical Animal Health and Production, 2025)

Determining the efficacy of phytoconstituents of Ficus religiosa L. against dermatophytes through invitro and insilico approaches - A. Anitha; P. Ponmurugan; V. Hemamalini; D. Arunkumar (In Silico Pharmacology, 2025)

Physiological basis and metabolite profiles of pre harvest sprouting resistance in rice varieties of Tamil Nadu - J. Deepika; D. Vijayalakshmi; Santosh Ganapati Patil; S. Vellaikumar; P. Arunkumar; V. Ravichandran; K. Thirukumaran (Cereal Research Communications, 2025)

Stilt floor optimization based on stiffness and column contribution - R. Kavitha; G. Keertiga; D. Suryakrishnan; N. Santhakrishnan; M. Arunkumar (Innovative Infrastructure Solutions, 2025)

Cleaner production of performance-enhanced hybrid composites using agro-industrial wastes: A sustainable waste management strategy - B. Prabhu; M. Prakash; N. Ramasamy; Viswanathan Kanagasabai; T. Mohanraj; D. Vijay; T. Arunkumar (Journal of Environmental Management, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Novel biosynthesized zinc selenite photocatalysts for enhanced degradation of oxytetracycline and Rhodamine B dye with antibacterial activity - A. Anitha; P. Ponmurugan; D. Arunkumar; C. S. Sumathi; M. Sathishkumar; T. Purushothaman (BioMetals, 2025)

Growth and productivity of Haematococcus pluvialis and Coelastrella saipanensis by photosystem modulation for understanding the heterotrophic nutritional strategy for bioremediation application - K. Nayana; Vaishnav S. Babu; D. Vidya; M.P. Sudhakar; Kulanthaiyesu Arunkumar (Environmental Research, 2024)

A rationally designed hetero-assembly of 2D/2D Nitrogen-doped MXene/Graphene via supercritical fluid processing for high energy durable supercapacitors - K. Nasrin; M. Arunkumar; N. Koushik Kumar; V. Sudharshan; S. Rajasekar; D. Mukhilan; M. Arshad; M. Sathish (Chemical Engineering Journal, 2023)

Mitigating abiotic stresses using natural and modified stilbites synergizing with changes in oxidative stress markers in aquaculture - D. Arunkumar; K. K. Krishnani; Neeraj Kumar; B. Sarkar; A. K. Upadhyay; P. B. Sawant; N. K. Chadha; R. Abisha (Environmental Geochemistry and Health, 2023)

Effect of Volume and Surface Area on Growth and Productivity of Microalgae in Culture System - K. Nayana; D. Vidya; K. Soorya; Aswathi Dineshan; Anaswara S. Menon; Rashida Mambad; K. Arunkumar (BioEnergy Research, 2023)

The impacts of Mn ion incorporation on the structural, optical, and magnetic properties of hematite NPs - S. James Jayaseelan; K. Parasuraman; D. Benny Anburaj; M. Jothibas; B. Arunkumar (Nanotechnology for Environmental Engineering, 2023)

Genetic Diversity and Population Structure in Fragmented Natural Populations of Melia dubia Cav. Revealed by SSR Markers—Its Implications on Conservation - Swati Rawat; Annapurna D.; Arunkumar A. N.; Geeta Joshi (Plant Molecular Biology Reporter, 2022)

Life history, phenology, host range and natural enemies of Acria meyricki Shashank and Ramamurthy (Lepidoptera: Depressariidae): an emerging defoliator of oil palm, Elaeis guineenis Jacq. In India - L. Saravanan; P. Kalidas; T. Phanikumar; D. Dwarakakumar; Ankita Gupta; R. Arunkumar (Phytoparasitica, 2020)

Phosphorus dynamics and solubilizing microorganisms in acid soils under different land uses of Lesser Himalayas of India - Ranjan Paul; Raj Deo Singh; A. K. Patra; D. R. Biswas; Ranjan Bhattacharyya; K. Arunkumar (Agroforestry Systems, 2017)

Hand, foot and mouth disease (HFMD): emerging epidemiology and the need for a vaccine strategy - S. Aswathyraj; G. Arunkumar; E. K. Alidjinou; D. Hober (Medical Microbiology and Immunology, 2016)

Implications of Volume Exclusion: A Look at Thermodynamic Perspective of DNA-Hemoglobin Complexes and Their Reconstitutes Under Macromolecular Crowding - Priyanka D. Pal; Prabhakar M. Dongre; Arunkumar V. Chitre (Journal of Fluorescence, 2016)

“Is Macromolecular Crowding Overlooked?”- Effects of Volume Exclusion on DNA-Amino Acids Complexes and Their Reconstitutes - Priyanka D. Pal; Prabhakar M. Dongre; Arunkumar V. Chitre (Journal of Fluorescence, 2014)